Corporate governance reform strategies for State-Owned Enterprises (SOEs): An integrated review of related literature - Admire Mthombeni (Indonesian Journal Of Business And Economics, 2021)
This review is centered on the corporate governance reform strategies for SOEs with a primary focus on Zimbabwean SOEs. The main objective of the review were to consider ways to enhance corporate governance practices by SOEs and corporate governance reform strategies adopted by SOEs. The authors also reviewed the literature on corporate governance of SOEs with the primary goal of identifying main strategies that may be used to reform SOEs that includes developing relevant corporate governance legislation. In fulfilling these objectives, authors used a qualitative literature analysis approach. The study reveals that corporate governance reform is necessary to rescue troubled SOEs who have been found under different situations of corporate governance malpractices. The authors recommended that in Zimbabwe there is a need for more SOEs corporate governance workshops. Researchers also laid out there is a need to carry out a further study on the effectiveness of corporate governance reform strategies being adopted by Zimbabwean SOEs that include the implementation of the PECG Act amongst other Acts of parliament that are meant to provide corporate governance of SOEs.  Authors recommended that further studies on the corporate governance of SOEs would be most desirable as a way of addressing the pertinent problems currently bedevilling such SOEs in Zimbabwe.